Study on the impact of Mozart's Sonata K448 on the extinction of fear memory in relation to the environment in female mice without dysbiosis (Research, Society and Development, 2024)
The fear memory is essential for survival, as is its extinction to avoid phobias and post-traumatic stress disorder. The objective of this article is to present results of an investigation into the interference of Mozart's Sonata K448 in the extinction of fear memory to a contextualized aversive environment in female mice. Methodology: for this purpose, 36 female mice of the C57BL/6J lineage were used and randomly divided in three groups: Mozart, Environment, and Control. The animals in the Mozart group were exposed to music from gestation to adulthood, while the other groups were only exposed to ambient sound. Behavioral procedures included music exposure, habituation, sound/shock conditioning training, extinction test, and recall test. Behavioral data were statistically analyzed. Results: the difference in freezing behavior between groups in the recall test (t(9)=0.874; p=0.405) was insignificant. The mean freezing percentage was 13.11% ± 2.26% for the Mozart group and 9.67% ± 3.37% for the Control group. Conclusion: from the results obtained, it’s possible to observe that female mice exposed to Mozart's Sonata K448 compared to the Control group showed no difference in the influence of music on the recall of fear memory. However, the limits of the "Mozart effect" are observed, highlighting the need to consider additional variables such as musical preference and experimental conditions when investigating the therapeutic effects of music.